MAP2K1 gene as potential blood-based biomarker for early detection of alzheimer's disease / Nur Alifah Shairah Johan Arifin - Johan Arifin, Nur Alifah Shairah (2014)
Background: Alzheimer' disease (AD) is the most common subtype of dementia which accounts for 60-80% of dementia characterized as a brain disorder usually affecting the elderly. It is associated with slow, progressive loss of function of the brain. By 2050, prevalence in Malaysia is expected to rise to 453,900 with annual new cases of 138,800. Though a variety of testing approaches are available, however, it is often difficult to make an accurate diagnosis of early stage of AD. There are currently no biochemical markers available for preclinical detection of definitive AD. MAP2K 1 is gene of interest for potential blood-based biomarker as it involves in signalling pathways which regulate various cellular activities such as proliferation, differentiation, survival and death. Impairment in control of MAPK signalling pathways has been shown to be implicated in AD. In this study, comparison of expression of MAP2Kl gene and correlation with previous microarray study have been established. Method: Phase 2 samples consist of a total of 30 samples of healthy, AD, MCI and VAD. Blood samples were collected and RNA extraction was conducted to generate cDNA. All blood samples were subjected to qPCR analysis. Relative quantification of the data obtained was analysed using Pfaffl' s mathematical model. The data obtained were correlated with previous microarray study. Results: Relative mRNA expression level in AD was upregulated 5.64-fold as compared to healthy subjects whereas for MCI and VA, it was downregulated 38-fold and 0.23-fold, respectively. As p<0.0001, there is significant difference in MAP2Kl expression between AD and other subtypes of dementia which are MCI and V AD. The direction of expression of MAP2Kl gene is following data obtained from previous microarray study. Conclusion: MAP2Kl gene was found to be a potential blood-based biomarker for early detection of Alzheimer's disease as it showed a significantly higher level of mRNA expression as compared to healthy, MCI and V AD.